Association of Vitamin D Deficiency with High-Sensitivity CRP and Arterial Stiffness in Patients with Hypertensive Heart Disease - Muhammad Hussain, Kamran Shauket, Mougheesa Baig, Amir Jalal, M. Shakil Zari Khawri Siddiqui, Waqas Qurshi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypertensive heart disease (HHD) is a major cardiovascular complication of long-standing hypertension and is characterized by progressive vascular remodeling, arterial stiffness, and low-grade systemic inflammation. Vitamin D deficiency has been increasingly implicated in endothelial dysfunction, inflammatory activation, and adverse cardiovascular outcomes; however, its relationship with inflammatory markers and arterial stiffness in patients with established hypertensive heart disease remains insufficiently explored. Objective: To evaluate the association of vitamin D deficiency with high-sensitivity C-reactive protein (hs-CRP) levels and arterial stiffness in patients with hypertensive heart disease. Methods: This cross-sectional analytical study was conducted from January 2022 to March 2023 at Sahiwal Teaching Hospital, Sahiwal, and Sugra Shafi Medical Complex, Narowal, Pakistan. A total of 100 adult patients with echocardiographically confirmed hypertensive heart disease were enrolled. Serum 25-hydroxyvitamin D [25(OH)D] levels were measured and categorized as deficient (<20 ng/mL), insufficient (20–29 ng/mL), or sufficient (≥30 ng/mL). Inflammatory status was assessed using hs-CRP. Arterial stiffness was evaluated by carotid–femoral pulse wave velocity (cf-PWV) and augmentation index. Statistical analysis included group comparisons, correlation analysis, and multivariable linear regression to determine independent associations. Results: Vitamin D deficiency was present in 56% of patients. Individuals with deficient vitamin D levels exhibited significantly higher hs-CRP concentrations and increased arterial stiffness compared with those having sufficient vitamin D (p<0.001). Serum 25(OH)D levels showed a significant inverse correlation with hs-CRP (r = −0.48), cf-PWV (r = −0.52), and augmentation index (r = −0.41). After adjustment for age, gender, body mass index, blood pressure, diabetes mellitus, duration of hypertension, renal function, and medication use, vitamin D levels remained an independent predictor of both hs-CRP and cf-PWV (p<0.001). Conclusion: Vitamin D deficiency is independently associated with increased systemic inflammation and arterial stiffness in patients with hypertensive heart disease. These findings suggest that low vitamin D status may contribute to vascular dysfunction and inflammatory burden in hypertensive cardiac pathology and highlight the potential value of vitamin D assessment in this high-risk population. Keywords: Vitamin D deficiency; Hypertensive heart disease; High-sensitivity C-reactive protein; Arterial stiffness; Pulse wave velocity; Inflammation